2021
DOI: 10.1016/s2352-3018(20)30300-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety, adherence, and HIV-1 seroconversion among women using the dapivirine vaginal ring (DREAM): an open-label, extension study

Abstract: Background The Ring Study, a phase 3 trial in 1959 sexually active women (randomised 2:1), showed a favourable safety profile and a 31% HIV-1 infection risk reduction for a vaginal ring containing 25 mg of dapivirine, compared with a placebo ring. We report here the DREAM study, which aimed to evaluate safety, adherence, and HIV-1 incidence in those using the dapivirine vaginal ring (DVR) in open-label use. Methods The DREAM study is an open-label extension of The Ring Study, done at five research centres in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…The studies included 51 countries, with 28 studies from Europe [33,34,37,39,40,43,, 47 from North and South America and Australia [29-32, 36, 38, 42, 47, 48, 72-113], 18 from the Asia-Pacific [35,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129], 17 from North and sub-Saharan Africa [10,28,44,46,[130][131][132][133][134][135][136][137][138][139][140][141][142][143], and 13 from multiple regions [41,45,[144][145][146][147][148...…”
Section: Resultsmentioning
confidence: 99%
“…The studies included 51 countries, with 28 studies from Europe [33,34,37,39,40,43,, 47 from North and South America and Australia [29-32, 36, 38, 42, 47, 48, 72-113], 18 from the Asia-Pacific [35,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129], 17 from North and sub-Saharan Africa [10,28,44,46,[130][131][132][133][134][135][136][137][138][139][140][141][142][143], and 13 from multiple regions [41,45,[144][145][146][147][148...…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of NNRTI resistance in HOPE and DREAM was 7 of 38 seroconversions (18.4%) and 5 of 18 seroconversions (28%), respectively (Fig. 2) [69 ▪ ,77]. Both full-length reverse transcriptase Sanger sequencing and UMI-NGS with a detection limit of 1% mutation frequency were conducted due to the association of reduced susceptibility to DAPY class inhibitors by C-terminal domain mutations [78,79], but no additional or novel HIV-1 mutations were found to be selected by DPV.…”
Section: Resistance With the Dapivirine Ringmentioning
confidence: 99%
“…A monthly silicone elastomer intravaginal matrix ring containing 25 mg of DPV (a diarylpyrimidine [DAPY] NNRTI) reduced the risk of HIV-1 infection among African women in the ASPIRE (MTN-020) and Ring (IPM 027) Phase III studies by 30% compared with placebo, and by an estimated 60% in the open label HOPE (MTN-025) and IPM DREAM studies [67,68 ▪ ,69 ▪ ,70]. Although the risk of breakthrough infection in younger women was greater in the trials due to low adherence, the open-label REACH (MTN-034) study showed higher rates of both ring acceptance (89%) and adherence (50%) in 16–21-year-old girls and young women.…”
Section: Resistance With the Dapivirine Ringmentioning
confidence: 99%
“…Single indication HIV-only prevention products are also in development. Importantly, after multiple clinical trials demonstrating efficacy, the dapivirine intravaginal ring for HIV prevention is in the process of gaining regulatory approval in individual countries (27)(28)(29)(30). Furthermore, long-acting injectable cabotegravir (CAB-LA) has completed phase 3 trials in men who have sex with men, transgender women, and cisgender women, showing strong efficacy and safety results (31,32).…”
Section: Opportunitiesmentioning
confidence: 99%